Ab initio study of the moisture stability of lead iodine perovskites. (6th August 2018) - He, Yunqiu; Wang, Si-Qin; Xue, Xiong-Xiong; Zhang, Lixin; Chen, Keqiu; Zhou, Wu-Xing; Feng, Yexin
Abstract: The stability of hybrid lead iodine perovskite in a humid environment has been a major obstacle to developing long-term photovoltaic devices. However, understanding the detailed degradation mechanism of lead iodine perovskite in moisture is still challenging. Herein, using first-principles calculations, we show that embedded water molecules will facilitate the decomposition of lead iodine perovskite. Alloying FAPbI3 and CsPbI3 to form mixed-cation lead iodine perovskites not only can optimize the tolerance factor to obtain better phase stability, but also can improve the moisture stability of them. With the accumulation of water molecules in the perovskite lattice, the optical absorption spectra show a blue-shift and decreased intensity, and the moisture stabilities of lead iodine perovskites are further lowered. The iodine vacancy in lead iodine perovskites can facilitate the water molecule migration and thus is a disadvantage in improving the moisture stability of them, which should be minimized during perovskite growth. These findings provide new insight in understanding the poor moisture stability of lead iodine perovskites, which should be helpful for the future design and optimization of stable perovskite solar cells.